PERANCANGAN SISTEM INFORMASI PENJUALAN DAN PENERIMAAN KAS PADA USAHA MEBEL: indonesia - Yustina Alfira Nay; Leopold Melkiano Triangga Dawu; Maria Odriana Veronica Moi (Jurnal Akuntansi Universitas Muhammadiyah Kupang, 2023)
Taruna Furniture is a manufacturing business that has been established for 15 years, producing interior furniture based on customer orders, but does not yet have a good sales and cash receipt system. Order data processing and sales transactions are still carried out in a simple manner, cash receipts are not recorded properly, there are no complete transaction archives, limited financial literacy of business owners, difficulty measuring business results, and income earned is directly used for daily needs. This research aims to design a sales and cash receipts information system that suits Taruna Furniture's needs in order to make work easier, produce the required reports and measure business results. The method used is piece analysis and system design through flow diagrams. The results of the research are in the form of a sales and cash receipts system design which is important to implement so that the Taruna Furniture business can continue to survive amidst business competition.